2009
DOI: 10.1111/j.1467-8624.2009.01266.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Extended Friendship Effects on Minority and Majority Children’s Interethnic Attitudes: A Longitudinal Study

Abstract: Longitudinal direct and extended cross-ethnic friendship effects on out-group evaluations among German (majority status, N = 76) and Turkish (minority status, N = 73) children (age 7-11 years) in ethnically heterogeneous elementary schools were examined at the beginning and end of the school year (time lag: 7 months). The results showed that among majority status children, but not minority status children, direct cross-ethnic friendship predicted over time positive out-group evaluations. This association was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
266
0
10

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 302 publications
(292 citation statements)
references
References 58 publications
16
266
0
10
Order By: Relevance
“…Accordingly, Feddes et al (2009) found that cross-ethnic friendships improved outgroup attitudes through perceived social norms which indicate crossethnic friendships as acceptable behavior in a multi-cultural environment. Similarly, the promotion of extended cross-ethnic friendship in which knowing that an ingroup friend has an outgroup friend lead to increases in positive intergroup relationships amongst children (Wright, Aron, McLaughlin-Volpe, & Ropp, 1997).…”
Section: Cross-ethnic Friendship Numbers and Qualitymentioning
confidence: 98%
See 2 more Smart Citations
“…Accordingly, Feddes et al (2009) found that cross-ethnic friendships improved outgroup attitudes through perceived social norms which indicate crossethnic friendships as acceptable behavior in a multi-cultural environment. Similarly, the promotion of extended cross-ethnic friendship in which knowing that an ingroup friend has an outgroup friend lead to increases in positive intergroup relationships amongst children (Wright, Aron, McLaughlin-Volpe, & Ropp, 1997).…”
Section: Cross-ethnic Friendship Numbers and Qualitymentioning
confidence: 98%
“…With the reformulation of the contact theory, more attention has been drawn to crossethnic friendships, which promote positive intergroup relations by providing long-term, mutual, and affective relationships that include self-disclosure, empathy and trust (Pettigrew, 1998;Turner et al, 2007). Empirical research has supported this assumption, and cross-ethnic friendships have consistently been found to improve positive outgroup attitudes among children and adolescents (e.g., Aboud et al, 2003;Feddes et al, 2009;Levin, Van Laar, & Sidanius, 2003;Pettigrew & Tropp, 2006). Supporting intergroup contact theory, propinquity, i.e.…”
Section: Cross-ethnic Friendships and Ethnic Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Ellison & P owers, 1994;Feddes, Noack, & Rutland, 2009;Pettigrew & Tropp, 2006;Quillian & Campbell, 2003;Reinders, 2011), konden andere onderzoekers die gevolgen van gemengd onderwijs niet vaststellen (zie bijv. Bakker, Denessen, Pelzer, V eneman, & Lageweg, 2007;Stark, 2011;Wagner, Hewstone, & Machleit, 1989), of vonden zelfs resultaten die als een weerlegging van de contacthypothese kunnen worden geïnterpreteerd (zie bijv.…”
unclassified
“…Accepted: 2012-10-17. Published: 2012 *Corresponding author at: School of Social Sciences, Universiti Sains Malaysia, 11800 Pulau Pinang, Malaysia, email: hashimah@usm.my This is an open access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.Friendships can be used as a measure to improve inter-group relations in society with different sub-groups.Friendship that exists among people from different groups can be associated with more positive inter-group attitudes (Pettigrew, 1998;Feddes, Noack, & Rutland, 2009). Ethnicity represents a major construct by which a society can be divided into.…”
mentioning
confidence: 99%